2022
DOI: 10.21203/rs.3.rs-1901358/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for E2SKAPE Infections and Mortality among Liver Transplant Recipients

Abstract: Introduction: Infections caused by Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp (ESKAPE) plus Escherichia coli (E2SKAPE), in particular multidrug-resistant (MDR) E2SKAPE infections, occur frequently and pose a life-threatening to liver transplant (LT) recipients. To prevent E2SKAPE infections and improve the prognosis of LT recipients, the identification of risk factors for E2SKAPE infections and mortality is necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…3 Numerous risk factors, including advanced age (>80 years), female gender, implant type, prior diagnoses of osteonecrosis and rheumatoid arthritis, revision surgery, aseptic stem mobilization, and the use of non-cemented stems, have been identified. [4][5][6] Reports from the Swedish Hip Arthroplasty Register have shown that the survival of non-cemented total hip arthroplasty is lower than that of cemented implants, partly due to a higher incidence of early periprosthetic fractures. 7 According to a meta-analysis by Jonathan N. Lamb et al in 2022, encompassing 4841 patients over the last decade, the mortality of patients succumbing to periprosthetic fractures stands at 3% at 30 days (2.4% during hospitalization), 5% at 90 days, and 13% at one year post-fracture.…”
Section: Introductionmentioning
confidence: 99%
“…3 Numerous risk factors, including advanced age (>80 years), female gender, implant type, prior diagnoses of osteonecrosis and rheumatoid arthritis, revision surgery, aseptic stem mobilization, and the use of non-cemented stems, have been identified. [4][5][6] Reports from the Swedish Hip Arthroplasty Register have shown that the survival of non-cemented total hip arthroplasty is lower than that of cemented implants, partly due to a higher incidence of early periprosthetic fractures. 7 According to a meta-analysis by Jonathan N. Lamb et al in 2022, encompassing 4841 patients over the last decade, the mortality of patients succumbing to periprosthetic fractures stands at 3% at 30 days (2.4% during hospitalization), 5% at 90 days, and 13% at one year post-fracture.…”
Section: Introductionmentioning
confidence: 99%